Analysis of Communication and Policy Information in Improving the Managerial Competence of Elementary School Principals in Banjarnegara District - Heling Suhono; Yahya Sudarya; Ine Kusuma Aryani (Green Publisher, 2024)
The competence of the school principal as a managerial person who manages the school as an educational organization plays a role in making plans as a goal for the school as an organization that aims to achieve the goals set by all school members. In carrying out school institutional activities, it cannot be separated from the coordination of institutions in the field of education that provide guidance and design policies, in this case the Department of Education, Youth and Sports in Banjarnegara Regency. However, the implementation of communication and information which should be able to be established well has not yet been fully realized. This research aims to analyze communication and policy information in improving the managerial competence of elementary school principals in Banjarnegara Regency. This research uses a descriptive qualitative approach. Data collection techniques were carried out by means of interviews, observation and documentation. Data analysis techniques are carried out by condensing data, displaying data and drawing conclusions and verification. The research results show that policy communication and information has been implemented well and effectively from the aspects of transmission, clarity and consistency. The school principal has good managerial competencies in accordance with the principles of leadership management, namely the ability to plan, organize, implement and supervise. In this way, communication and policy information can improve the managerial competence of elementary school principals in Banjarnegara Regency.